Penerapan Metode Quality Function Deployment (QFD) untuk Meningkatkan Produk Penutup Baterai Mesin Mixing di Industri Otomotif - Tambunan, Erwin Barita Maniur; Nuryono, Arif (Universitas Katolik Parahyangan, 2025)
Manufacturing companies in the injection molding sector supply plastic-based automotive spare parts such as car battery covers. The mixing process at this company is still done manually because the previous mixing machine was not functioning properly. The problem with a mixing machine is that it produces an uneven mixture. Apart from that, the mixing machine does not yet have a component that functions to filter tin flakes that are mixed into the crusher material. This research aims to reduce the percentage of uneven mixing defects and increase the impeller rotation to the maximum in the mixing process. This research uses the Quality Function Deployment (QFD) method combined with the Fishbone diagram method and the 5W+1H method. This research found that uneven mixing defects during the mixing process were dominant in this problem. After analysis, there was a problem with the distribution of impeller rotation, the maximum was only 0.134 m/s or around 60% of the total material mixing. Redesigned improvement solutions for the mixing process by modifying the mixing machine with more sophisticated technology. This research resulted in a reduction in production defects from 9% to 2% and an expansion of impeller rotation in the mixing process, up to a maximum of 0.202m/s or a flatness of around 90%.